The value of the benefits of mediation in the settlement of child custody cases in court - Jasmaniar, Jasmaniar; Alam, Syamsul (Institut Agama Islam Negeri Kendari, 2025)
This article is to analyze the value of the benefits of mediation in child custody cases.This research is normative research with a statutory approach and a conceptual approach. Types and sources of legal materials are primary legal materials, secondary legal materials and tertiary legal materials. Searching for legal materials uses the literature study method to search for legal materials, including regulations governing mediation, child custody, journals and literature books. The collected materials are then inventoried and identified and all existing legal materials are systematized. The results of the research show that the integration of mediation is based on the provisions of Article 130 HIR & Supreme Court Regulation No. 1 of 2016 concerning Mediation Procedures in Court requiring that cases be resolved through mediation including child custody. This method of resolving cases will prioritize the interests of the child because it is through a peace agreement which is confirmed by a deed. peace will enable joint parenting of children, this method will provide benefits in the child's growth and development even though the parents are divorced